2015
DOI: 10.1093/nar/gkv952
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian splicing factor SF1 interacts with SURP domains of U2 snRNP-associated proteins

Abstract: Splicing factor 1 (SF1) recognizes the branch point sequence (BPS) at the 3′ splice site during the formation of early complex E, thereby pre-bulging the BPS adenosine, thought to facilitate subsequent base-pairing of the U2 snRNA with the BPS. The 65-kDa subunit of U2 snRNP auxiliary factor (U2AF65) interacts with SF1 and was shown to recruit the U2 snRNP to the spliceosome. Co-immunoprecipitation experiments of SF1-interacting proteins from HeLa cell extracts shown here are consistent with the presence of SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 90 publications
(159 reference statements)
2
38
0
1
Order By: Relevance
“…Recent genome-wide BP mapping studies indicate that a large proportion of introns have more than one BP, generally clustered in close proximity in relation to the 3′ splice site [ 27 , 38 ], although a BP could be found in rare case further upstream of a 3′ splice site [ 27 , 38 ]. Since the predicted -51C [ 11 ] from the 3′ splice site of intron 8 identified by ESEfinder [ 34 ] or by Human Splice Finder [ 28 ] was not mapped as an authentic BP in this study, our data imply that the observed mutations (-435 C-to-A and -51 C-to-G) in the mt BRAF pre-mRNA might disrupt the binding of trans -acting factors, such as SRSF6 (SRp55) [ 11 , 39 , 40 ] and SF3b/3a [ 41 45 ], to the -51 region and thereby prevent the recruitment of SF1 and U2 snRNA [ 46 48 ] to select an authentic distal BP for splicing of BRAF RNA. Consequently, loss of splicing factor binding to the -51 region and activation of a proximal BP usage might lead to skipping of exons 4–8 in splicing of mt BRAF.…”
Section: Resultsmentioning
confidence: 86%
“…Recent genome-wide BP mapping studies indicate that a large proportion of introns have more than one BP, generally clustered in close proximity in relation to the 3′ splice site [ 27 , 38 ], although a BP could be found in rare case further upstream of a 3′ splice site [ 27 , 38 ]. Since the predicted -51C [ 11 ] from the 3′ splice site of intron 8 identified by ESEfinder [ 34 ] or by Human Splice Finder [ 28 ] was not mapped as an authentic BP in this study, our data imply that the observed mutations (-435 C-to-A and -51 C-to-G) in the mt BRAF pre-mRNA might disrupt the binding of trans -acting factors, such as SRSF6 (SRp55) [ 11 , 39 , 40 ] and SF3b/3a [ 41 45 ], to the -51 region and thereby prevent the recruitment of SF1 and U2 snRNA [ 46 48 ] to select an authentic distal BP for splicing of BRAF RNA. Consequently, loss of splicing factor binding to the -51 region and activation of a proximal BP usage might lead to skipping of exons 4–8 in splicing of mt BRAF.…”
Section: Resultsmentioning
confidence: 86%
“…One of the RBPs that has been implicated in cancer and a neurodegenerative disease, but has not been studied in great detail, is RNA-binding motif protein 17 (RBM17) (15,16). Originally identified as a component of the spliceosome complex, it interacts with splicing factors U2AF2, SF1 and SF3B1 (17)(18)(19); our lab has also discovered that RBM17 binds Ataxin-1 in a polyglutamineand phosphorylation-dependent manner (15). Limited studies on the splicing functions of RBM17 so far have suggested a role in alternative splicing.…”
Section: Introductionmentioning
confidence: 99%
“…SURP domains interact with SF1, and G-patch domains were shown to activate RNA helicases for ATP hydrolysis. Both domains are required for BP recognition by the SF3B1-containing U2 snRNP [103][104][105]. These findings strongly suggest that SUGP1 is involved in the BP recognition process.…”
Section: Sf3b1mentioning
confidence: 72%